2021
DOI: 10.1038/s41598-021-89498-5
|View full text |Cite
|
Sign up to set email alerts
|

Cues to gender and racial identity reduce creativity in diverse social networks

Abstract: The characteristics of social partners have long been hypothesized as influential in guiding group interactions. Understanding how demographic cues impact networks of creative collaborators is critical for elevating creative performances therein. We conducted a randomized experiment to investigate how the knowledge of peers’ gender and racial identities distorts people’s connection patterns and the resulting creative outcomes in a dynamic social network. Consistent with prior work, we found that creative inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Redundancy: Finally, in a related context, in the field of creative ideation, it has been reported that inspirees stimulated by highly creative alters, tend to generate more creative ideas [47][48][49]. However, as a group, the inspirees ideas was found to be similar to each other leading to redundancy in generated ideas over time at the group level.…”
Section: B Novelty Innovation and Redundancymentioning
confidence: 99%
“…Redundancy: Finally, in a related context, in the field of creative ideation, it has been reported that inspirees stimulated by highly creative alters, tend to generate more creative ideas [47][48][49]. However, as a group, the inspirees ideas was found to be similar to each other leading to redundancy in generated ideas over time at the group level.…”
Section: B Novelty Innovation and Redundancymentioning
confidence: 99%
“…Unfortunately, despite its ubiquity, the temporal self-organization characteristic of social networks has received rather little research attention when it comes to novel idea-generation performances of humans. Recent explorations suggest two opposing factors that influence idea generation performances in this setting ( 10 , 11 ). On the one hand, people selectively seek inspiration from (or "follow", as referred to henceforth) the high-performing peers in their networks.…”
Section: Introductionmentioning
confidence: 99%
“…To address these, we use a recently developed experimental approach that facilitates conducting randomized controlled experiments in the temporal social network setting ( 10 , 11 ). The experiment design builds on ego-centric networks, which specifically map the social inspiration ties from the perspective of a single person (an “ego”) to their peers (“alters”).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation